Wheat, barley, oat and corn silage rations for growing steers - Bolsen, K.; Oltjen, J.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Eleven wheat, barley, oat and corn silages were evaluated in two steers growing trials in 1975 and 1976. In both trials, steers fed barley or corn silages had similar rate and efficiency of gains. Also, barley and corn silages supported greater performance than any of the seven wheat or oat silages. In the 1976 trial steers fed Trio or Lodi oat silage had the lowest feed consumption and made the slowest and least efficient gains. For an average of the two trials barley and corn silages had similar feeding values. Wheat silages had 90 and 80% the relative feeding value of corn silage in 1975 and 1976, respectively. Oat silages had only 48% the feeding value of corn silage in 1976.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Wheat; Barley; Oat; Corn; Silage; Steers